Synchrony of Caresses: Does Affective Touch Help Infants to Detect Body-Related Visual–Tactile Synchrony? - Della Longa, Letizia; Filippetti, Maria Laura; Dragovic, Danica; Farroni, Teresa (Frontiers in Psychology, 2020)
Bodily self-awareness, that is the ability to sense and recognize our body as our own, involves the encoding and integration of a wide range of multisensory and motor signals. Infants’ abilities to detect synchrony and bind together sensory information in time and space critically contribute to the process of gradual bodily self-awareness. In particular, early tactile experiences may have a crucial role in promoting self-other differentiation and developing bodily self-awareness. More specifically affective touch, slow and gentle touch linked to the neurophysiologically specialized system of C-tactile afferents, provides both information about the body from within (interoception) and outside (exteroception), suggesting it may be a key component contributing to the experience of bodily self-awareness. The present study aimed to investigate the role of affective touch in the formation and modulation of body perception from the earliest stages of life. Using a preferential looking task, five-month-old infants were presented with synchronous and asynchronous visuo-tactile body-related stimuli. The socio-affective valence of the tactile stimuli was manipulated by means of the velocity (CT-optimal [slow] touch vs CT-suboptimal [fast] touch) and the source of touch (human hand vs brush). For the first time, we show that only infants that were stroked using a brush at slow velocity displayed a preference for the visual-tactile synchronous video, suggesting that CT-optimal touch might help infants to detect body-related visual-tactile synchrony, independently from the source of touch. Our results are in line with findings from adults and indicate that affective touch might have a critical role in the early development of bodily self-awareness.